Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jam.15539
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the antifungal activities of three essential oils as alternative therapies in dermatophytosis infections

Abstract: Aims This work examines the available scientific evidence about the efficiency of essential oils (EO) as an alternative therapy to traditional treatment of fungal infections, including onychomycosis, assessing the effect of the three EO most frequently studied for their antifungal activity (thyme, cinnamon and tea tree EO) against three causative agents of fungal diseases in humans: Trichophyton rubrum, Trichophyton mentagrophytes complex and Candida albicans. Methods and Results The PRISMA statement protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Overall, we can summarize our findings that lemongrass and cinnamon have significantly better efficacy than tea tree, except for the concentration of 100 %, and their effect did not dependent on the tested concentration. The efficacy was the highest possible and the zone inhibition Despite promising results of recent studies [6,33,50], we agree with their authors that the potential toxicity of these products must be considered because EO have been shown to cause skin allergy and irritation. As a result, it is critical not only to investigate the effectiveness of essential oils, but also pay attention to their safety (harmlessness) as well as the potential associated risks.…”
Section: T a O Et Al Confirmed That Essential Oil Fromsupporting
confidence: 81%
“…Overall, we can summarize our findings that lemongrass and cinnamon have significantly better efficacy than tea tree, except for the concentration of 100 %, and their effect did not dependent on the tested concentration. The efficacy was the highest possible and the zone inhibition Despite promising results of recent studies [6,33,50], we agree with their authors that the potential toxicity of these products must be considered because EO have been shown to cause skin allergy and irritation. As a result, it is critical not only to investigate the effectiveness of essential oils, but also pay attention to their safety (harmlessness) as well as the potential associated risks.…”
Section: T a O Et Al Confirmed That Essential Oil Fromsupporting
confidence: 81%
“…The activities found were dose-dependent with significant cytotoxicity at concentrations of ≥10% [ 78 ]. Despite these results, a recent meta-analysis showed that TTO had a limited antifungal effect ( Trichophyton rubrum , Trichophyton mentagrophytes complex, and C. albicans ) when compared to other EOs ( Cinnamomum zeylanicum and Thymus vulgaris ) [ 79 ]. Thus, the use of TTO against dermatophytes would not be advisable.…”
Section: Biological Properties Of Ttomentioning
confidence: 99%
“…The two major classes used are azole, topical drugs (i.e., tioconazole, clotrimazole, oxiconazole, econazole, miconazole) and systemic azole agents (fluconazole, itraconazole) and allylamine (terbinafine and naftifine) [ 150 ]. Promising results are obtained with alternative antifungal agents such as epigallocatechin 3-O-gallate (EGCg) [ 159 , 160 ] and plant essential oils [ 161 , 162 , 163 ].…”
Section: Fungal Infectionsmentioning
confidence: 99%